Analisis Pelaksanaan Pemenuhan Kebutuhan Perumahan Bagi Masyarakat Berpenghasilan Rendah Di Kota Palembang - Hermawita, Hermawita; Idris, Umiyati; Zofir, Tasrif (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The purpose of this objectives to research the implementation of housing desires for low-profits groups inside the town of Palembang. This studies is a descriptive research with a qualitative technique. The information used is based totally on the kind of quantitative information and qualitative records even as based totally on the source is number one facts and secondary records. The facts collection gadgets used had been commentary, interviews and documentation. The informants in this take a look at had been the top of the branch of Housing and settlement regions of South Sumatra Province; Head of Housing department; Head of Housing Provision phase; Civil servant staff and honorarium as many as 3 people; and coffee-earnings groups as many as three human beings. statistics evaluation is a qualitative analysis with an interactive version. based on the effects of the have a look at, it is able to be concluded that the implementation of the fulfillment of housing wishes for low-profits communities within the city of Palembang has been carried out optimally.